PENGARUH PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DINAS PENDIDIKAN KABUPATEN NIAS SELATAN - Selestina Febriani Gea (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This research aims to determine the effect of job training on employee performance at the South Nias Regency Education Office. This type of research is causal quantitative research and the data source is primary data. The population used in this research was 47 employees, while the sample used was 32 employees using Slovin's theory, namely the sampling formula. The research instrument was measured using a Likert scale. The data analysis method used is simple linear regression analysis. Data testing uses data processing tools, namely SPSS 22.0 for Windows. In this study, a simple linear regression equation was obtained, namely Y= 18.505 + 0.590X, the value of t_(count) (5.670) >〖t〗_tabel (1.697) with a significance level of 0.000 < 0.05. Then the value obtained for the job training variable influencing employee performance variables or R square (R2) is 0.517 (51.7%). So the decision is H_( a) accepted H_( o) rejected, so it can be concluded that job training has a positive and significant effect on employee performance at the South Nias District Education Office.